An empirical study on the impact of digital platform usage on sports consumption behavior based on the theory of planned behavior - Le, Yu; Latif, Rozita Binti Abdul; Zid, Azlina (Edelweiss Applied Science and Technology, 2025)
This study aims to examine how digital platform usage influences sports consumption behavior by integrating it into the Theory of Planned Behavior (TPB), emphasizing the mediating role of consumption intention. A quantitative approach was adopted, collecting 318 valid responses from Chinese users of digital platforms related to sports. Structural Equation Modeling (SEM) was employed to test the hypothesized model, including confirmatory factor analysis and bootstrapping to examine mediation effects. Results show that subjective norms, attitudes, and digital platform usage all significantly predict sports consumption intention. Attitude exhibited the strongest effect on intention. Consumption intention, in turn, significantly influences actual sports consumption behavior. Notably, digital platform usage does not directly affect consumption behavior but exerts an indirect effect through intention. The mediating role of intention was confirmed in all proposed pathways. Digital platforms shape sports consumption behavior primarily by influencing users’ psychological intentions rather than direct behavioral activation. The findings suggest that platform operators and sports marketers should focus on enhancing user intention through positive attitudes and social influence, rather than solely promoting direct transactions.